Analisis Kurikulum Merdeka dan Peran Pendampingan Keluarga dan Guru/Dosen dalam Mengatasi Learning Loss di Masa Pandemi Covid-19 - Yasin Yasin; Dedi Romli Triputra; Hilda Kumala Wulandari; Titi Rahmawati (Jurnal Ilmiah Wahana Pendidikan, 2022)
The family is a social institution that is universal and multifunctional, which functions as supervision, social, educational, religious, protection, and recreation. Parents are also specifically directly involved in school activities so that they can know firsthand the progress of children's learning both in terms of cognitive, affective and conative through regular meetings, discussions through social media groups and mandatory programs such as being a member of the school committee, program character building and extracurricular activities that can be monitored directly by parents. The COVID-19 pandemic poses challenges in the educational aspect that result in Learning Loss. The purpose of this research article is to review several education policies launched by the government in overcoming Learning Loss. One of the government policies is related to the learning process and curriculum implementation. This study provides an overview of the independent curriculum and examines the success rate of the independent curriculum in overcoming Learning Loss by providing three different characteristics from the previous curriculum, namely project-based learning, focusing on essential materials and learning flexibility. The research method used is a literature study that reviews various sources of government policy with problem tree analysis as identification and mapping of alternative solutions. Thus the results of the study indicate that the application of the "Free Curriculum" at the education unit level can reduce Learning Loss during the COVID-19 pandemic.